2006
DOI: 10.1186/1471-2458-6-180
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel surveillance for human enterovirus 71 in Sarawak, Malaysia: lessons from the first 7 years

Abstract: Background: A major outbreak of human enterovirus 71-associated hand, foot and mouth disease in Sarawak in 1997 marked the beginning of a series of outbreaks in the Asia Pacific region. Some of these outbreaks had unusually high numbers of fatalities and this generated much fear and anxiety in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
167
5
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(188 citation statements)
references
References 23 publications
14
167
5
2
Order By: Relevance
“…Consistent with previous reports in other countries and regions, [1,9,10] the majority of HFMD cases (accounting for approximately 90% of total cases) in mainland China were children under 5 years old, with the peak incidence occurring at 1−3 years of age ( Figure 1). As a common febrile illness of early childhood, enteroviral infection occurred mainly among preschool-aged children.…”
Section: Resultssupporting
confidence: 79%
“…Consistent with previous reports in other countries and regions, [1,9,10] the majority of HFMD cases (accounting for approximately 90% of total cases) in mainland China were children under 5 years old, with the peak incidence occurring at 1−3 years of age ( Figure 1). As a common febrile illness of early childhood, enteroviral infection occurred mainly among preschool-aged children.…”
Section: Resultssupporting
confidence: 79%
“…This finding is probably because our expanded surveillance detected more patients with neurologic disease. Since 1997, multiple cases of EV71 infection have been associated with severe aseptic meningitis and pulmonary edema in the Asia–Pacific region, including Taiwan, Malaysia, Singapore, and Japan ( 26 , 32 37 ). In addition, E30 was the second most common genotype detected during this period in this study and in previous studies from other countries; Asia and European countries reported that E30 was the predominant genotype ( 1 , 4 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several outbreaks have also been recorded in Australia (Gilbert et al, 1988;Sanders et al, 2006;McMinn et al, 2001b). Co-circulation of EV71 and CVA16 has contributed to serious HFMD outbreaks in China in (Zhang et al, 2009), Taiwan in 1998(Lin et al, 2003), and Malaysia in 1997(Podin et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Several outbreaks have also been recorded in Australia (Gilbert et al, 1988;Sanders et al, 2006;McMinn et al, 2001b). Co-circulation of EV71 and CVA16 has contributed to serious HFMD outbreaks in China in (Zhang et al, 2009), Taiwan in 1998(Lin et al, 2003), and Malaysia in 1997(Podin et al, 2006.The enterovirus genome is a positive ssRNA molecule of approximately 7500 nt, comprising a single ORF flanked 59Abbreviations: CVA16, coxsackievirus A16; EV71, enterovirus 71; HEV, human enterovirus; HFMD, hand-foot-and-mouth disease; PV, poliovirus; UTR, untranslated region.The GenBank/EMBL/DDBJ accession numbers for the 59UTR sequences of EV71 and CVA16 are GU236109-GU236113 and GU236100-GU236108, respectively; and for the VP1 sequences are FJ868281 and GU142870-GU142873, and FJ868280, GU142867-GU142869 and GU232771-GU232775, respectively. and 39 by untranslated regions (UTRs).…”
mentioning
confidence: 99%